Carbon-rich cycles with two and more 1,3-butadiyne units: syntheses, structures and reactivities - Gleiter, Rolf; Werz, Daniel B. (Carbon-rich compounds, 2006)
This chapter contains sections titled: Introduction Syntheses 1,3-Butadiyne Moieties as Spacers and Framework Reactivity Base-induced Prototropic Rearrangements Elimination Reactions Reductions of Cyclic 1,3-Butadiynes Acid-induced Transannular Reactions Spectroscopic and Structural Investigations Structural Investigations NMR Spectroscopic Investigations Photoelectron and Electron Absorption Spectra of Cyclic 1,3-Diynes Concluding Remarks and Outlook Experimental: Selected Procedures General Procedure for the Preparation of N,N'-Dialkyl-1,8-diazacyclotetradeca-3,5,10,12-tetraynes (27a-e) General Procedure for the Cadiot-Chodkiewicz Coupling During the Syntheses of Azacyclotetraynes 10(n) General Procedure for the Preparation of the Tetrachalcogenacyclo-tetraynes 29(n) and 33(n) and Hexachalcogenacyclohexaynes 34(n) and 35(n) General Procedures for the Preparation of Hexadiyne-bridged Macrobicycles Alternative A Alternative B
Gesehen am 21.10.2020